A microwave-based sensor for non-contact measurement of water and crude oil mixture volume ratios - Mayet, Abdulilah Mohammad; Mohammed, Salman Arafath; Hanus, Robert; Qamar, Shamimul; Loukil, Hassen Loukil; Shukla, Neeraj K. (Metrology and Measurement Systems, 2026)
This work presents the design, fabrication, and characterization of a novel microwave-based sensor utilizing multiple U-shaped resonators for non-contact measurement of volume percentages in water-crude oil mixtures. The sensor, fabricated on an RT/Duroid 4003 substrate (εr = 3.55, thickness 0.787 mm), operates in the 2–2.3 GHz frequency range with a maximum insertion loss of 0.97 dB. Design optimization and electromagnetic simulations were performed using ADS software followed by experimental validation with 10 ml samples of varying water content (0–100%) placed in a 3D-printed PLA container. Significant shifts in center frequency and response prominence were observed, enabling clear differentiation of mixture compositions. The sensor achieved a high sensitivity of 4.12 MHz/εr , surpassing many prior designs, while the non-contact configuration enhances practicality by minimizing contamination risks and interference. Although highly sensitive and compact, potential limitations include dependence on crude oil composition variability, temperature effects, and the fixed sample volume used in testing. These results demonstrate the sensor’s reliability for real-time fluid analysis, with promising applications in petroleum, chemical, and environmental monitoring industries.